1994
DOI: 10.1523/jneurosci.14-09-05202.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of NMDA-R1 subunit immunoreactivity in the visual cortex of adult and neonatal rats

Abstract: NMDA receptor activation can alter synaptic strength, cause cell death, and may modulate the release of glutamate and other neurotransmitters. Using a specific and selective antiserum directed against the R1 subunit of the NMDA receptor, we examined (1) whether NMDA receptors in the adult rat visual cortex are exclusively postsynaptic or also presynaptic and (2) whether NMDA-R1 subunits are incorporated into the plasma membrane prior to, contemporaneously, or following the formation of synapses during postnata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
148
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(171 citation statements)
references
References 53 publications
21
148
2
Order By: Relevance
“…Gold label occurred postsynaptically, directly over, or near the PSD complex and also within the cytoplasm of dendritic spines. These locations agree with results from past ultrastructural studies (Aoki et al, 1994;Charton et al, 1999;Conti et al, 1999;Kharazia and Weinberg, 1999;Valtschanoff and Weinberg, 2001). In addition, NR2B subunit labeling was prominent in the cytoplasm and along membranes of presynaptic terminals.…”
Section: Discussion Nr2b Subunits Occur Both Pre-and Post-synapticallysupporting
confidence: 92%
See 2 more Smart Citations
“…Gold label occurred postsynaptically, directly over, or near the PSD complex and also within the cytoplasm of dendritic spines. These locations agree with results from past ultrastructural studies (Aoki et al, 1994;Charton et al, 1999;Conti et al, 1999;Kharazia and Weinberg, 1999;Valtschanoff and Weinberg, 2001). In addition, NR2B subunit labeling was prominent in the cytoplasm and along membranes of presynaptic terminals.…”
Section: Discussion Nr2b Subunits Occur Both Pre-and Post-synapticallysupporting
confidence: 92%
“…It has been shown that layer I contains more synapses with NMDA receptors than deeper layers (Aoki et al, 1994); therefore, we predicted that a great amount of synapses would be affected by the D-APV application in this layer. Earlier published work (Aoki et al, 2003) showed that, indeed, the effect of D-APV upon NR2A subunits is restricted to layer I during the first 2 h of surface application of the drug.…”
Section: Analysis Of Nr2b Immunolabeling In Layer Imentioning
confidence: 97%
See 1 more Smart Citation
“…A possible complication to our interpretation of the data is that presynaptic NR2B-containing NMDARs are known to exist (Aoki et al, 1994) and to enhance neurotransmitter release in the visual cortex (Sjostrom et al, 2003). The deprivation-induced elevation in NR2B proteins within the lysed synaptic membrane fraction (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Sublamination requires postsynaptic activation of NMDA receptors, which are present and involved in synaptic potentiation in the developing LGN (Mooney et al, 1993). Whereas presynaptic NMDA receptors may be present in visual cortex (Aoki et al, 1994), there is no evidence for their presence in the LGN. Physiological evidence suggests that NMDA receptors are postsynaptic, because holding postsynaptic LGN cells at hyperpolarizing membrane potentials reduces the NMDA component of the postsynaptic current (Esguerra et al, 1992;Ramoa and McCormick, 1994).…”
Section: Discussionmentioning
confidence: 99%